Evaluation of In Vitro Production Capabilities of Indole Derivatives by Lactic Acid Bacteria - Bingyang Ma; Yan Zhao; Liping Liu; Jianguo Xu; Qingping Hu; Saisai Feng; Liangliang Zhang (Microorganisms)
Lactic acid Bacteria (LAB) convert tryptophan to indole derivatives and induce protective IL-22 production in vivo. However, differences in metabolizing capabilities among LAB species have not been widely investigated. In the present study, we compared the capabilities of 186 LAB strains to produce four kinds of indole derivatives, including indole-3-carboxaldehyde (IAId), indole-3-lactic acid (ILA), indole-3-propanoic acid (IPA), and indole-3-acetic acid (IAA). These strains were isolated from fermented foods, dairy products, and the feces of healthy individuals, as well as from fish and shrimp from Shanxi and Jiangsu provinces. They represent 15 genera, including Bifidobacterium, Enterococcus, Lacticaseibacillus, Lactiplantibacillus, Lactobacillus, Lactococcus, Limosilactobacillus, Pediococcus, Streptococcus, Weissella, Latilactobacillus, Levilactobacillus, Ligilactobacillus, and Loigolactobacillus. The results indicate widespread IAId-producing capabilities in LAB strains, with positive rates of approximately 90% (106/117) and 100% (69/69) among strains from Shanxi and Jiangsu provinces, respectively. The concentrations of IAId ranged from 72.42 ng/mL to 423.14 ng/mL in all positive strains from Shanxi Province and from 169.39 ng/mL to 503.51 ng/mL in strains from Jiangsu Province. Intriguingly, we also observed specific ILA-producing capabilities in Lactiplantibacillus strains, with positive rates of 55.17% (16/29) and 80.95% (17/21) among strains isolated from Shanxi and Jiangsu provinces, respectively. The overall detection rates of ILA among all tested strains (including both Lactiplantibacillus and other genus strains) were 17.9% (21/117) and 26.1% (18/69). The concentrations of ILA in positive strains ranged from 12.22 ng/mL to 101.86 ng/mL and from 5.75 ng/mL to 62.96 ng/mL from Shanxi and Jiangsu provinces, respectively. IPA and IAA were not detected in any strains. Finally, these indole derivative-producing capabilities were not related to their geographical origins or isolation sources. The current study provides insights into the species- or genus-dependent capabilities for metabolizing indole derivatives. Defining the specific roles of LAB in indole derivative metabolism will uncover the exact physiological mechanisms and be helpful for functional strain screening.